Pengembangan dan Pengujian Performa Progressive Web App pada Sistem Reservasi Ruangan Fakultas Teknik Universitas Sam Ratulangi - Veronica Waeo; Alwin Melkie Sambul; Salaki Reynaldo Joshua (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The manual room reservation process at the Faculty of Engineering, Sam Ratulangi University leads to uncertain application status, scheduling conflicts, and limited transparency. Existing reservation practices also lack offline accessibility and installable web capabilities. This study aims to develop and evaluate a Progressive Web App (PWA)-based room reservation system to improve accessibility while maintaining performance. The system was developed using the Rapid Application Development method and evaluated through automated black box testing with Selenium and performance testing using Google Lighthouse. Performance measurements were conducted on four representative pages using Google Chrome and Lighthouse under online and offline scenarios, with each test repeated three times on the same desktop environment. The PWA achieved average performance scores of 100 for cache-offline and cache-online scenarios, 98.5 for no-cache offline, and 96 for no-cache online. The non-PWA version achieved average scores of 99.75 and 96.25 under online conditions but could not function offline. These results demonstrate that the proposed PWA provides installation capability and limited offline access while maintaining online performance comparable to a conventional web application, making it a practical solution for room reservation services in higher education.